QUALITY ENHANCEMENT OF TOMATOES (Lycopersicum esculentum Mill.) USING GIBBERELLIC ACID (GA) FROM VARIOUS PLANT MATERIALS - Mayadewi, Ni Nyoman Ari; Astawa, Nyoman Gede (International Journal of Biosciences and Biotechnology, 2022)
Tomato (Lycopersicum esculentum Mill.) is a fruit with many benefits. Plant growth regulators (PGRs) prove effective in improving the quality and production of tomatoes. Gibberellic Acid/GA is a PGR that stimulates the process of flowering, parthenocarpy, and carbohydrate mobilization during germination and influences other plant physiological aspects. However, because synthetic GA is costly, numerous natural ingredients have been proposed as its source, for example, bamboo shoots, vegetable ferns, corns, and shallots that can improve the quality of tomatoes. This study aimed to determine the role of natural GA from various plant extracts on the quality of tomatoes, providing recommendations for the best extract to improve the quality of tomatoes. It was conducted in the experimental garden at the Agronomy and Horticulture Laboratory, Physiology Laboratory of the Faculty of Agriculture, and Food Analysis Laboratory of the Faculty of Agricultural Technology, Udayana University. This research was compiled using a Randomized Group Design consisting of one factor, i.e., the type of natural extract with five settings and four repetitions. The tomato plant treatments were E0 = no extract sprayed, BE = sprayed with bamboo shoot extract, VE = vegetable fern extract, OE = onion extract, and CE = corn extract. The results showed that gibberellins from natural ingredients significantly affected fruit diameter, fruit thickness, and total sugar content of tomatoes. The best tomatoes were obtained by applying onion extract as a source of natural gibberellins.